Analyzing the Effect of COVID-19 on the Disbursement Rates of Department of the Interior and Local Government: A Comparative Study of Pre- and Post-Pandemic Periods - Stephanie Lorien C. Lebrillo; Aristeo C. Salapa (East Asian Journal of Multidisciplinary Research, 2023)
Early in 2020, the COVID-19 epidemic broke out, causing unprecedented changes in businesses and society worldwide, including in the Philippines. This study aims to examine the effect of the COVID-19 epidemic on the disbursement rates of the Department of the Interior and Local Government. By comparing the pre-pandemic and post-pandemic periods from 2017 to 2022, the study seeks to shed light on the extent of the pandemic's impact on the effectiveness and efficiency of financial resource allocation within the government sector. This comparative study, which uses statistical techniques and quantitative data analysis, sheds significant insight into the Philippine government's challenges with managing its expenditures before and after the pandemic.